Revitalisasi Peran Guru Agama dalam Membangun Kampung Keluarga Sakinah di Kuripan Yosorejo Pekalongan Selatan Kota Pekalongan - Ridho Riyadi; Setyawan M Adin; Pratama Ilham Wahyu; Jayanti Dwi (LP3M STAI Darussalam Krempyang Nganjuk, 2022)
The Sakinah family is the goal of marriage. To build a family that ends in sakinah requires many roles, including the role of a religious teacher in the community who becomes a reference in dealing with problems in the household. However, in the midst of the COVID-19 pandemic, many family strengthening activities did not run because they did not allow face-to-face meetings. This service activity aims to strengthen the motivation of religious teachers in building a sakinah family in Pekalongan City. BP4 (Advisory Board for the Guidance and Preservation of Marriage) Pekalongan City has tutors who become extension workers at the kelurahan level consisting of religious teachers, community leaders. The main problem experienced by BP4 Pekalongan City is the lack of enthusiasm for tutors in building a sakinah family in the midst of the covid 19 pandemic and the vacuum of pre-marital briefing activities for prospective husband and wife during the covid 19 pandemic. The solution to the first problem is to organize a revitalization of the role of religious teachers, while the solution to the second problem is pre-marital debriefing for prospective husband-wife couples online using the Google Meet and Messenger platforms.